Influence of Vitafort and Lactobifadol Probiotics on Excremental Microbiocenoses of Turkey Poults - Ayrat Khabirov1 , Fail Khaziakhmetov1 , Yaroslav Rebezov2,4, Olga Gorelik2 , Marina Derkho3 , Valeri (Institute of Medico-legal Publications Pvt Ltd, 2020)
The article presents the results of research on the use of probiotics “Vitafort” at a dose of 0.5 ml (107 CFU / g) and “Laktobifadol” at a dose of 0.2 g per 1 kg of live weight in the turkeypoults breeding, which ensured the development of beneficial intestinal microflora, increased preservation turkey poults, an increase in the digestibility of raw protein and nitrogen-free extractive substances, nitrogen absorption, improvement of hematological and biochemical blood parameters and, ultimately, an increase in live weight and intensity of turkey poults by 9.2 and 12.5%.